Formation conditions of allivalites, olivine-anorthite crystal enclaves, in volcanics of the Kuril-Kamchatka Arc. - Plechov, Pavel Yu; Shishkina, T A; Ermakov, V A; Portnyagin, Maxim V (PANGAEA, 2008)
In this paper allivalites, coarse- and giant-textured olivine-anorthite rocks occurring as separate blocks in the eruption products of many volcanoes from the frontal part of the Kuril-Kamchatka Arc are under consideration. New data are reported on petrography, mineralogy, and composition of melt inclusions in minerals from ten allivalite samples collected at Ksudach, Ilinsky, Zavaritsky, Kudryavy, and Golovnin Volcanoes. Crystallization temperatures of allivalite minerals were estimated as 970-1080°C at melt water content of 3.0-3.5 wt % and oxygen fugacity NNO=1-2. Genetic connection was established between compositions of melt inclusions and interstitial glasses in allivalites and volcanic rocks. Cumulate nature of allivalites was demonstrated. Using mass balance calculations, degree of fractionation of primary melts during formation of cumulate layers was estimated for various volcanoes as 22-46%.
Composition of melts and minerals from volcanic rocks of the Kuril-Kamchatka Arc
Keywords: Archive of Ocean Data; ARCOD; Golovnin Volcano, Kunashir Is., Kuril Islands; Golov-vlc; Ilinsky Volcano, Kamchatka; Ilin-vlc; Ksudach Volcano, Kamchatka; Ksud-vlc; Kudr-vlc; Kudryavy Volcano, Iturup Is., Kuril Islands; Zavaritsky Volcano, Simushir Is., Kuril Islands; Zavar-vlc